The Influence of Empowering Leadership and Compensation System Mediated by Employee Intrinsic Motivation on Turnover Intention at PT IMIP Bahadopi Regency Central Sulawesi - Ayuandira, Ririn; Kussudyarsana, Kussudyarsana; Waskito, Jati; Wajdi, Farid (International Journal of Management Science and Information Technology, 2023)
This study analyzes the effect of empowering leadership and compensation systems mediated by Employee Intrinsic Motivation on Turnover Intention at PT. Industrial Morowali Industry Park Bahadopi Regency, Central Sulawesi, while the research method used is quantitative correlation analysis using SMART PLS 3 with 166 employee samples as a result of removing outliers. The results of this study indicate that Empowering leadership, Compensation system, and Employee intrinsic motivation have a positive and significant effect on Turnover Intention, Empowering Leadership, Compensation system has a positive and significant effect on Employee intrinsic motivation then Empowering leadership, Compensation system has a positive and significant effect on Turnover intention mediated by Employe intrinsic motivation.